Experimental Comparison of Ground Plane Detection Speed Across Mobile Platforms - Ladiesga, Laura; Pranata, Caraka Aji (Journal of Applied Informatics and Computing, 2026)
Markerless Augmented Reality (AR) technology has become increasingly important in various applications, yet its performance varies significantly across different platforms. This study conducts a comparative experimental analysis of ground plane detection performance between iOS and Android platforms using the Vuforia-based KreasiFurniture application. The research examines detection speed under varying lighting conditions (indoor and outdoor) and camera distances (50 cm, 100 cm, and 150 cm) through systematic testing with five repetitions per condition. Data were analyzed using Three-Way ANOVA with IBM SPSS Statistics 25. Results demonstrate that iOS achieves significantly faster and more consistent detection (mean = 1.402 seconds, SD = 0.143) compared to Android (mean = 1.541 seconds, SD = 0.235), with a statistically significant difference of 0.139 seconds (p = 0.003). The optimal detection distance was found at 100 cm for both platforms (p = 0.018). While lighting conditions showed no significant main effect (p = 0.129), a significant Platform × Light interaction (p = 0.038) was revealed, indicating that iOS maintains stable performance across lighting variations, whereas Android experiences substantial performance degradation in indoor conditions. These findings provide practical recommendations: iOS is preferable for applications requiring consistent indoor performance, 100 cm represents the optimal interaction distance for both platforms, and Android deployments should implement adaptive strategies for variable lighting conditions.